Standards and global trade : a voice for Africa - Abiola, Victor O.; Wilson, John S.; World Bank. (Washington, D.C. : World Bank, 2003)
Providing an in-depth analysis of five African countries - Kenya, Mozambique, Nigeria, South Africa and Uganda, this volume provides a resource of information and guidance for policymakers, the development community and others in a critical new ""behind the border"" barrier to trade.
Includes bibliographical references and index.
rua 14/06/17
Loan
Keywords: Exports; Export marketing; Quality control; Africa